A review of species recognition in the Phenacoccus aceris species-group (Hemiptera: Coccomorpha: Pseudococcidae) using molecular and morphological data - Wang, Xu-Bo; Wu, San-An (Zootaxa, 2017)
The maple mealybug, Phenacoccus aceris (Signoret) (Hemiptera: Pseudococcidae), is a widespread polyphagous pest. The taxonomy of P. aceris and some congeners is controversial. This study utilized molecular analysis of one mitochondrial (cytochrome oxidase I) and two nuclear (EF-1α and 28S D2D3) genes, and morphological data, to investigate the P. aceris species-group based on 120 individuals collected from 16 localities in China. Analyses of the nucleotide sequence data recovered four well-supported clades that enabled us to reassess the taxonomic utility of some morphological characters used for species recognition in the P. aceris species-group, such as the number, location and width of circuli, and the distribution pattern of oral-collar tubular ducts on the dorsum. Polymorphism in the number of circuli indicated that this character-state alone is unreliable for species separation, but a combination of the number, location and relative width of the circuli provides a significant taxonomic character. The distribution of oral-collar tubular ducts on dorsal segments of the cephalothorax can be used also for species separation. In addition, specimens that keyed morphologically to P. aceris contained three putative species that are not separated by host-plant preferences. These putative species are genetically and morphologically different from P. aceris in France (the type locality of P. aceris) and are thus probably new to science. A network analysis of the COI haplotypes showed that the hosts Fraxinus spp. (Oleaceae) and Zanthoxylum bungeanum (Rutaceae) in North China are attacked by both P. aceris and P. azaleae, so previous identifications of this group based on the identity of these host plants is misleading. The taxonomic confusion in the P. aceris species-group may be due to the co-occurrence of multiple putative species.